KOSAKATA PERALATAN RUMAH TANGGA TRADISIONAL MASYARAKAT MELAYU DI SINGKAWANG - Handayani, Pratiwi; Patriantoro, Patriantoro; Amir, Amriani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractTraditional Home Appliances are equipment or various tools available at home and used by the community according to their respective traditions. This research focuses in the semantic field, namely analyzing data on traditional household appliances based on the form, lexical meaning, cultural meaning, and semantic role of traditional Malay household vocabulary in Singkawang, especially in Semelagi Kecil Kelurahan. The method used in this research is descriptive method with a qualitative research form. The data source in this study is the Singkawang dialect Malay spoken by native speakers of the Semelagi Kecil Kelurahan. The techniques used in this study are listening, competent, note taking, and recording. Data collection tools in this study are interview guides, notebooks, stationery and mobile phones. Based on research conducted, researchers have collected 65 vocabularies of traditional household appliances in the Singkawang dialect Malay. Overall data obtained from the interview process and video. The results of data analysis in the form of classified based on the name of the tool in the form of phonetic writing, then each tool is described in tabular form. The results of data obtained based on the lexical meaning are analyzed by referential analysis techniques or see a reference source in the form of a dictionary. The results of the data obtained based on cultural meanings were analyzed by means of cultural context analysis techniques in which this analysis presents the philosophy of each piece of equipment. The results of data analysis based on semantic roles were analyzed using vocabulary function techniques.Â Keywords: Vocabulary, Traditional Home Appliances, Semantic